An information sources map for Occupational and Environmental Medicine: guidance to network-based information through domain-specific indexing. - Silverstein, S. M. (American Medical Informatics Association, 1993)
This paper describes a prototype information sources map (ISM), an on-line information source finder, for Occupational and Environmental Medicine (OEM). The OEM ISM was built as part of the Unified Medical Language System (UMLS) project of the National Library of Medicine. It allows a user to identify sources of on-line information appropriate to a specific OEM question, and connect to the sources. In the OEM ISM we explore a domain-specific method of indexing information source contents, and also a domain-specific user interface. The indexing represents a domain expert's opinion of the specificity of an information source in helping to answer specific types of domain questions. For each information source, an index field represents whether a source might provide useful information in an occupational, industrial, or environmental category. Additional fields represent the degree of specificity of a source in individual question types in each category. The paper discusses the development, design, and implementation of the prototype OEM ISM.